The history of Urdu literature (from Beginning to 1857) in an Interdisciplinary perspective - Muhammad Zeshan Wakeel; DR. Safeer Hyder (بازیافت, 2021)
Dr. Tabassum Kashmiri is one of the most important contemporary writers. He is a modern poet but his real identity is his written history - "The history of Urdu literature (from early to 1857)". In the present era, we get to read many Urdu literary histories. One of them is the written history of Tabassum Kashmiri, which has been formed with the help of interdisciplinary studies. This article discusses "The history of Urdu literature (from early to 1857) in an inter-disciplinary perspective.